Fumonisin and ochratoxin-producing strains of Aspergillus section Nigri are associated with onion (Allium cepa L.) bulbs sold in markets in southwest Nigeria - Catherine Oluwakemi Esuola; Alejandro Ortega-Beltran (Frontiers in Fungal Biology)
IntroductionOnion bulbs are edible, nutritious vegetables and spices. In Nigeria, mass propagation of onion seedlings is limited due to infection of the onion bulbs by Aspergillus section Nigri, especially Aspergillus niger strains. Mycotoxin-producing A. niger strains are detrimental to public health. Hence, this study was undertaken to screen the locally sourced onion bulbs for fumonisin B2 (FB2) [Multiplex A: fum6 (374 bp), fum8 (272 bp), fum13 (168 bp), and fum19 (479 bp) and Multiplex B: fum1 (452 bp), fum7 (238 bp), fum3 (173 bp), and fum14 (321 bp)] and ochratoxin A [OTA; pks15ks (776 bp)] A. niger biosynthetic genes.MethodsThus, 100 onion bulbs were collected from four different local markets (Dugbe, Agbowo, Sasa, and Omi). The surface of each bulb was disinfected, and after incubation, isolates of A. niger were detected. A. niger isolates were cultured on potato dextrose agar. Genomic DNA was extracted from isolates of A. niger. Multiplex PCR confirmed the presence and absence of FB2 (fum) and OTA (pks15ks) biosynthetic genes.Results and DiscussionA total of 200 isolates of A. niger were isolated from the onion bulbs, and 22 (11%) isolates amplified at least two fum genes, while three (1.5%) amplified the pks15ks gene. All isolates were positive for fum1 and fum19. The highest/lowest percentage of the location/isolates of fum and pks15ks was Agbowo/Omi with 32.0%/2.1% and Dugbe/Agbowo with 6.7%/2.3%, respectively. Hence, the use of multiplex PCR to detect FB2 and OTA biosynthetic genes in the isolated A. niger strains from the locally sourced onion bulbs will assist onion growers in the mass production of healthy onion seedlings with export potential and quality. Early detection of FB2 and OTA biosynthetic genes is important to predict possible mycotoxin-producing A. section Nigri in onion bulbs.